2014
DOI: 10.1179/1743282014y.0000000124
|View full text |Cite
|
Sign up to set email alerts
|

Defence responses ofAphanoregma patens(Hedw.) Lindb. to inoculation withPythium aphanidermatum

Abstract: We examined the defensive responses of leaf surfaces, rhizoids, and protonemata of the moss Aphanoregma patens (Hedw.) Lindb. to inoculation with zoospores and encysted zoospores (cysts) of the oomycete Pythium aphanidermatum OPU849. Aphanoregma patens infected with Pythium exhibited extensive browning of the leaves and stems 4 days after inoculation. The zoospore infection sites were rhizoids and protonemata. Cysts on the rhizoids and protonemata germinated and formed elongated hyphae that invaded the cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Several pathogens of vascular plants, such as the bacteria Erwinia spp. (Andersson et al, 2005; de Leon et al, 2007; de Leon and Montesano, 2013; Machado et al, 2015; Alvarez et al, 2016) and fungi belonging to the oomycete Pythium (Oliver et al, 2009; Takikawa et al, 2015; Castro et al, 2016) and Botrytis (de Leon et al, 2012; Castro et al, 2016), cause disease symptoms and expression of disease-associated genes that encode pathogenesis-related proteins when artificially inoculated to the moss P. patens (Hedw.) Bruch & Schimp.…”
Section: Introductionmentioning
confidence: 99%
“…Several pathogens of vascular plants, such as the bacteria Erwinia spp. (Andersson et al, 2005; de Leon et al, 2007; de Leon and Montesano, 2013; Machado et al, 2015; Alvarez et al, 2016) and fungi belonging to the oomycete Pythium (Oliver et al, 2009; Takikawa et al, 2015; Castro et al, 2016) and Botrytis (de Leon et al, 2012; Castro et al, 2016), cause disease symptoms and expression of disease-associated genes that encode pathogenesis-related proteins when artificially inoculated to the moss P. patens (Hedw.) Bruch & Schimp.…”
Section: Introductionmentioning
confidence: 99%
“…To exploit the advantages of P. patens as a model host plant, several pathogens have been tested for their ability to infect P. patens. For the fungal pathogens Botrytis cinerea, Altenaria brassicicola, Altenaria alternata, Fusarium avenaceum and Fusarium oxysporum (Ponce de Léon et al, 2007;Akita et al, 2011;Bressendorff, 2012;Lehtonen et al, 2012b;Ponce de Léon et al, 2012), the bacterium Pectobacterium carotovorum (Andersson et al, 2005;Ponce de Léon et al, 2007) and three species of the oomycete genus Pythium (Oliver et al, 2009;Takikawa et al, 2015), it has been shown that they are capable to infect P. patens. More recently, Reboledo et al (2015) described the infection of P. patens by the hemibiotrophic pathogen, Colletotrichum gloeosporioides.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal elicitor is a mechanism which induces plant phytoalexin and causes plant hypersensitivity or self -defense reaction during the physiological processes of plant disease resistance (Sangeetha et al 2015,Takikawa et al 2015, Zhang et al 2015. There is a long history of research of fungal elicitor-induced metabolite accumulation of taxol inTaxus chinensis (Pilger) Rehd.by activated spores of Cytoospora abiotis and Penicillium minioluteum dating back to the early 1990s (reference).Different kind of fungal elicitors are applied for the metabolite synthesis in medical plants (Table 1).…”
Section: Fungal Elicitormentioning
confidence: 99%